Towards p-11B medium configurations with high Pfus/PBrems ratios - Daponta, C.; Moustaizis, S.; Eliezer, S.; Henis, Z.; Lalousis, P.; Nissim, N.; Schweitzer, Y. (Frontiers in Physics, 2024)
Aneutronic p-11B nuclear fusion is promising for clean energy production, as it produces three (3) alpha particles with 8.7 MeV total energy. However, the main difficulty for p-11B fusion ignition (Q = Pfus/PBrems≥ 1) concerns the nuclear cross section and thus, reactivity efficiency at higher than 200 keV medium temperatures. To overcome this difficulty, the present work emphasizes on the numerical investigation of medium schemes (configurations) with enhanced reactivity. The configurations refer to the addition of energetic protons in a low-density 11boron or proton–11boron medium (n = 1020 m−3), with (np/nB) > 1 for Bremsstrahlung losses optimization and initial temperature in the range of 1 keV ≤ Tin≤ 400 keV. A self-consistent multi-fluid global particle and energy balance code, including collisions between all medium species (p, 11B, e, α), is used for the description of the temporal evolution of all fusion medium physical parameters and the evaluation of the optimum initial conditions for the obtainment of Q ≥ 1. The numerical simulation results show that the coupling between the 200 keV < Ep,0≤ 750 keV energetic protons and the 1 keV ≤ Tin≤ 400 keV initial fusion medium leads to ignition, 1 ≤ Q < 1.4, below Tin= 100 keV. In all the presented initial medium temperature cases, and especially, the lower (<) than 100 keV, the ignition condition (Pfus/PBrems) > 1 arises, as a consequence of the chain reactions and the related avalanche alpha heating effect.